Learning During the Covid-19 Pandemic through Progressive Muscle Relaxation Therapy - Muhammad Khabib Burhanudin Iqmah; Livana PH (Global Health Science Group, 2021)
The Covid-19 pandemic has impacted all sectors of life and all walks of life. The education sector is one of the most affected by the COVID-19 pandemic. Lectures during the pandemic using distance learning / online. The research design used a quasi experiment with a pre post test without a control group. The number of samples is 163 students in Kendal Regency with purposive sampling technique. The research data was collected using the Depression Anxiety and Stress Scale 21 (DASS 21) questionnaire. The research location is in Kendal Regency. The age of the youngest respondent is 18 years and the oldest is 50 years, the majority are female as many as 148 respondents (90.8 %), There is an effect of providing progressive muscle relaxation technique intervention on reducing stress levels with p value 0.000 (p < 0.05). Prompt treatment using the right way will help deal with stress. Unresolved stress will have an impact on health and productivity in life. Progressive muscle relaxation techniques can be used to reduce stress levels and relieve stress.